Kiss number 8 - Venable, Colleen A. F (First Second, an imprint of Roaring Brook Press, 2019)
"Mads is pretty happy with her life. She goes to church with her family, and minor league baseball games with her dad. She goofs off with her best friend Cat, and has thus far managed to avoid getting kissed by Adam, the boy next door. It's everything she hoped high school would be... until all of a sudden, it's not. Her dad is hiding something big--so big it could tear her family apart. And that's just the beginning of her problems: Mads is starting to figure out that she doesn't want to kiss Adam... because the only person she wants to kiss is Cat. Just like that, Mad's tidy little life has gotten epically messy--and epically heartbreaking. And when your heart is broken, it takes more than an awkward, uncomfortable, tooth-clashing, friendship-ending kiss to put things right again. It takes a whole bunch of them."--Page [2] of cover.